Barriers and supporters of home care implementation for the elderly in developing countries: A scoping review - Sulardi Sulardi; Nila Alfa Fauziah; Novalia Efrianty (International journal of health sciences, 2026)
Home care is an approach that has the potential to support aging in place, but its implementation faces various barriers at the individual, family, health worker, community, organizational, financing, and policy levels. This scoping review aims to map evidence on barriers and supporting factors for the implementation of home care for older adults in developing countries in the literature over the past ten years. The scoping review uses the Joanna Briggs Institute (JBI) framework and the PRISMA-ScR reporting principles. The population is older adults, the concept is home care/home-based care/community-based care and related services, and the context is developing countries or low- and middle-income countries (LMIC). The literature search was directed at PubMed/MEDLINE, Scopus, CINAHL, ScienceDirect, Web of Science, and Google Scholar for publications from 2016–2026. The evidence mapping indicates that the main barriers include limited health workers, lack of competence and training, limited resources, transportation and geographic distance, financing, weak regulations and referral systems, burden on family caregivers, low health and digital literacy, and coordination issues between organizations. Supporting factors include leadership, cross-sector collaboration, family and community involvement, community health workers, training and supervision, financing, home modifications, technology support, and integration of home care with primary health care services.